Field evaluation of palm oil adjuvanted feed-based streptococcosis vaccine efficacy in red hybrid tilapia - Mohammad Ridzuan, Mohd Syafiq; Abdullah, Azila; Nawi, Mohd Firdaus; Ramli, Norazsida; Mohd Yusof, Hanan (Department of Fisheries Malaysia, 2022)
Vaccination plays an important role in the aquaculture industry to prevent disease outbreaks, thereby ensuring an economically viable industry. A field trial was conducted in Pedu Lake, Kedah, to determine immunoglobulin M (IgM) progression in red hybrid tilapia following oral vaccination with palm oil adjuvanted streptococcosis vaccine. A total of 6,000 tilapias of 60 ± 20 g were selected and divided into three groups of single booster, double booster, and control group in duplicate. The single booster group was vaccinated orally at weeks 0 and 2, while fish of the double booster group were vaccinated at weeks 0, 2, and 6. Fishes from the control group were not given any vaccine throughout the experimental period. Samples of eye, brain, and kidney were collected at two weeks intervals for sixteen weeks cumulative to isolate the bacteria, while serum samples were collected to determine the antibody level. Throughout the study period, no outbreaks of streptococcosis were recorded, and none of the groups studied showed the presence of Streptococcus agalactiae. Very low mortality of single booster, double booster, and control group was noted at 2.1 ± 8.5 %, 1.3 ± 2.8 %, and 1.5 ± 7.1 %, respectively. Both vaccinated groups showed significant (p<0.05) increases in IgM antibody levels following immunization of first and booster doses before going down below the cut-off value six weeks post-vaccination in the single booster group. However, IgM antibody levels in the fish from the double booster group remained high until the end of the trial. In conclusion, oral vaccination with palm oil adjuvanted feed-based streptococcosis vaccine stimulates an adequate systemic immune response, which can confer possible protection against streptococcosis.